Phytochemical screening, antibacterial and antioxidant activities of Bryum billardieri and Rhodobryum giganteum from Mt. Data, Bauko, Mountain Province - Alonzo, Erika Angelyn M.; Lacerna, Ma. Zhannis T.; Santiago, Jasmin II C.
Mosses contain active constituents that exhibit various biological activities such as antibacterial, anti-inflammatory as well as antioxidant. Qualitative and quantitative phytochemical tests were done in two Bryaceae species, Bryum billardieri and Rhodobryum giganteum collected from Mt. Data, Bauko, Mountain Province. Carbohydrates, saponins, terpenoids, phytosterols, and phenolics were present in B. billardieri while R. giganteum also gave positive reaction for these constituents except for saponins, in addition to tannins and proteins. For the antibacterial activity, out of six species of bacteria, E. coli and S. aureus showed greater resistance to both extracts and controls used as compared to B. subtilis, S. typhi, P. vulgaris and M. luteus. The zones of inhibitions caused by B. billiardieri and the negative control have no significant difference as observed among all the bacterial species. R. Giganteum, on the other hand, had significant difference in antibacterial activity on B. subtilis and P. vulgaris against negative and positive control implying moderate antibacterial activity of the species. The test for Minimum Inhibitory Concentration of R. giganteum revealed bacteriostatic effect at 100 percent concentration. For the antioxidant activity, DPPH radical scavenging activity of Ascorbic acid, B. billardieri and R. aganteum were tested and effective concentration or EC50 values were determined to be 0.0007, 0.0621, and 3.4654, respectively. Values for EC50, the concentration needed to reduce initial amount of radicals to half were found to be significantly different from each other with the order R. giganteum, B. billiardieri and Ascorbic acid in increasing antioxidant activity -- Author's abstract.